1999
DOI: 10.1111/j.1469-7793.1999.579ae.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrectomy induces impaired insulin and glucagon secretion: evidence for a gastro‐insular axis in mice

Abstract: Hormones released from the digestive tract have been suggested to contribute to the metabolic disposal of ingested glucose. Thus, an oral glucose load is metabolized more rapidly than an intravenous glucose load, and more insulin is secreted after oral glucose than after an equivalent intravenous glucose load (McIntyre et al. 1964;Dupr e, 1991; Creutzfeldt & Nauck, 1992). Several intestinal hormones, including glucagon-like peptide_1-(7-36)-amide (GLP_1) and glucose-dependent insulinotrophic peptide (GIP), ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 37 publications
4
39
0
Order By: Relevance
“…This has been studied previously in GX mice and in isolated pancreatic islets from GX mice [14]. From these data, we have suggested that the impairment might reflect the loss of a gastric regulatory peptide that serves to enhance the insulin response to oral as well as circulating glucose [14]. In that study we could show that the impaired insulin response to glucose in GX mice was associated with an enhanced responsiveness to cholinergic agents and to agents stimulating cAMP formation [14].…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…This has been studied previously in GX mice and in isolated pancreatic islets from GX mice [14]. From these data, we have suggested that the impairment might reflect the loss of a gastric regulatory peptide that serves to enhance the insulin response to oral as well as circulating glucose [14]. In that study we could show that the impaired insulin response to glucose in GX mice was associated with an enhanced responsiveness to cholinergic agents and to agents stimulating cAMP formation [14].…”
Section: Introductionsupporting
confidence: 58%
“…This has been studied previously in GX mice and in isolated pancreatic islets from GX mice [14]. From these data, we have suggested that the impairment might reflect the loss of a gastric regulatory peptide that serves to enhance the insulin response to oral as well as circulating glucose [14].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…10 min prior to i.p. glucose injection of 1.2 g/kg with or without MRS2211 (50 mg/kg) i.p., and blood samples were collected at 0, 3, 10 and 40 min post glucose administration as previously described [27].…”
Section: Insulin and Glucagon Secretion From Islets In Vitromentioning
confidence: 99%